Antibiofilm Effect of Lavandula multifida Essential Oil: A New Approach for Chronic Infections - Jorge Alves-Silva; Mónica Zuzarte; Carlos Cavaleiro; Lígia Salgueiro (MDPI AG, 2023)
Fungal infections are associated with high morbidity and mortality rates, being highly prevalent in patients with underlying health complications such as chronic lung disease, HIV, cancer, and diabetes mellitus. To mitigate these infections, the development of effective antifungals is imperative, with plants standing out as promising sources of bioactive compounds. In the present study, we focus on the antibiofilm potential of Lavandula multifida essential oil (EO) against dermatophyte strains and Candida albicans. The EO was characterized using GC and GC-MS, and its antifungal effect was assessed on both biofilm formation and disruption. Biofilm mass, extracellular matrix, and viability were quantified using crystal violet, safranin, and XTT assays, respectively, and morphological alterations were confirmed using optical and scanning electron microscopy. L. multifida EO showed very high amounts of carvacrol and was very effective in inhibiting and disrupting fungal biofilms. The EO significantly decreased biofilm mass and viability in all tested fungi. In addition, a reduction in dermatophytes' extracellular matrix was observed, particularly during biofilm formation. Morphological alterations were evident in mature biofilms, with a clear decrease in hypha diameter. These promising results support the use of L. multifida EO in the development of effective plant-based antifungal products.